Role of biomarkers in early detection of anastomotic leakage and follow up of patients with colorectal surgery managed by enhanced recovery protocol - Essa, Mohamed S.; Abdelaal, Mohamed K.; Zayed, Mohamed E.; Mshantat, Abdulrahman M.; Salama, Ahmed M. F.; Ahmad, Khaled S. (International Surgery Journal, 2021)
Background: Anastomotic leakage (AL) considered as the most feared complication after colorectal resection surgery increasing morbidity, mortality and risk of recurrence among these patients. Therefore, early detection of AL is crucial. Biomarkers as procalcitonin (PCT), C-reactive protein (CRP), white blood cell count (WCC) provide an easy, safe and efficient methods for early detection of AL and follow up of the patients after discharge. Methods: This study included 130 patients presented with colonic or rectal cancer in the period from January 2018 to January 2021. This study was conducted in general surgery department, faculty of medicine, Benha university hospital. CRP, PCT and WBC count were measured pre-operatively, first, third, fifth and 7th day post-operative to detect the change in their levels when AL was diagnosed either by clinical, radiological or operative measures. Results: Among 130 patients, only 10 patients had AL. On POD-3, CRP and WCC values were significantly increased in AL patients while PCT was significantly elevated only from POD-5. The best cut-off value for CRP on POD-3 was >30.1 mg/l, reaching 90% sensitivity and 100% specificity for detecting AL while for WCC was >7.1× 109 cell/l, with 90% sensitivity and 72% specificity. The best cut-off value for PCT was in POD-5 which was >1.7 ng/ml with 100% sensitivity and 84% specificity. Conclusions: The analysis of CRP and WCC on POD-3 together with PCT serum concentrations on POD-5 is crucial for early detection of anastomotic leakage in either open or laparoscopic colorectal resection surgery.